ANALYSIS OF INDIVIDUAL FACTORS INFLUENCING THE SUCCESSION OF TIGASERANGKAI VILLAGE GOVERNMENT LEADERS WEST NIAS DISTRICT - Iman Suryani Daeli; Meiman Hidayat Waruwu; Odaligoziduhu Halawa; Eliyunus Waruwu (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
Leadership succession in villages is a change of leaders who play a role in continuing and developing village development programs. This phenomenon often faces obstacles due to a lack of clear planning, causing village communities to have difficulty understanding the direction of development and evaluating achievements. The problem formulation in this research is how individual factors influence succession. This research aims to identify and analyze individual factors that influence leadership succession in Tigaserangkai Village, West Nias Regency. The urgency of this research lies in the importance of an in-depth understanding of the factors that influence leadership for better village development planning. The research method used is qualitative, with data collection techniques through interviews, observation, and documentation. Data was analyzed descriptively and qualitatively. The research results show that the age and education of village leaders are important indicators of experience, wisdom, and ability to bring about positive change, while integrity, justice, and ethics are considered essential in building community trust. Leaders with a combination of education and strong moral character are considered more effective. In Tigaserangai Village, the balance between the leader's maturity and energy provides an adaptive perspective to change, while age and experience provide stability. The practical implementation of this research is the need to pay attention to the factors of age, education, and moral character in selecting village leaders. The limitation of this research is the limited sample which only covers one village. The next research recommendation is to conduct a comparative study in several villages to obtain broader generalizations regarding individual factors in village leadership succession.